Comparative Effectiveness of an FDA-Authorized Digital Therapeutic to Medications and Cognitive Behavioral Therapy Treating Chronic Insomnia in Adults. (April 2022) - Forma, Felicia; Pratiwadi, Ramya; El-Moustaid, Fadoua; Smith, Nathaniel; Velez, Fulton
Abstract: Introduction: Chronic insomnia affects the physical and mental health, quality of life, and productivity of 6 to 10% of the adult population (15-25 million U.S. adults). Available treatments include guideline-recommended first-line cognitive behavioral therapy for insomnia (CBT-I) and medications. However, limitations such as patient access to CBT-I and limited efficacy, the presence of significant side effects, as well as safety concerns about medications limit favorable outcomes. Somryst is an FDA-authorized prescription digital therapeutic for the treatment of chronic insomnia in adults. The purpose of this analysis is to compare the effectiveness of the digital therapeutic vs CBT-I and medications for primary insomnia. Methods: Chronic insomnia trials focused on digital therapeutic, CBT-I, or medication were identified in a systematic literature review. Studies using a comparator arm that cannot be considered clinically equivalent to other treatments in the network were excluded (eg, meaningfully different definition of placebo arm). A Bayesian network meta-analysis was performed in R on the mean change from baseline and the proportion of remitters using the insomnia severity index (ISI) endpoint with follow-up timepoints between 6 and 12 weeks. Mean change in ISI score from baseline was analyzed as a continuous endpoint while comparisons of the proportion of remitters were performed using odds ratios. The analysis used a random-effects model for the base case analysis. A surface under the cumulative ranking curve (SUCRA) analysis was performed to rank the treatments on each endpoint. Results: In total, 13 studies reported ISI mean change from baseline data. Only the digital therapeutic and CBT-I were significantly different than placebo. The digital therapeutic had the greatest mean change from baseline in ISI from placebo (−5.77 points, 95% Credible Interval (CrI) [−8.53, −3.07]), followed by CBT-I (−4.3 points, 95% CrI [−6.32, −2.39]). In the SUCRA analysis, the digital therapeutic had the highest probability (56%) of being the most effective treatment based on ISI mean change from baseline. Only 8 studies reported the proportion of ISI remitters. Only the digital therapeutic showed a statistically significant difference in remission vs placebo and had the highest odds ratio for remission vs placebo (12.33 95% CrI [2.28, 155.91]). The odds ratio for remission vs placebo in CBT-I was not statistically significant (4.08 95% CrI [0.45, 45.58]). The digital therapeutic had the highest probability (64%) of being the most efficacious for inducing remission per ISI. Conclusions: Somryst was projected to be the most effective therapy on both mean change in ISI and ISI remission within 6 to 12 weeks of treatment start vs either CBT-I or medications. Further investigation should be performed to demonstrate the long-term effectiveness of all chronic insomnia treatments. Funding: Pear Therapeutics